Technological and Economic Analysis on the Hungarian Rice Sector - Apáti, Ferenc (Acta Agraria Debreceniensis, 2003)
Hungary lies on the northern edge of rice production area. According to this, the climatic conditions area not perfect for this species. The production area of rice involves typically the poorer quality soils, however these meet the requirements of rice. In Hungary exclusively domestic types are grown which have high yield and good quality and these are usually wore successful than foreign types. On the other hand, these Hungarian types should be improved considering safety in production. Nowadays, rice is grown in large scale companies with 300-1400 hectares, where production technology already exists, machinery is suitable, however the latter one a little bit old. The average yields of the analysed companies were 3-4 t/ha in the past few years, which were a little bit above the national averages. The operating cost per hectare is almost 200 thousand HUF, from which the main part is the cost of machinery (35%) and the material cost (34%). The main part of the latter one is the irrigation costs (30%). The average cost, calculated from the total production cost, is 80 thousand HUF/t. Considering the above-mentioned costs and the price of rice (75 thousand HUF/t) it can be stated that the profitability of the rice sector is not the best, the cost rated profitability is -6.6%. According to the results of this analysis possibilities for the increase in profitability and improvement are increased subsidies and market price, as well as genetic improvement.